Functional elucidation of antibacterial phage ORFans targeting Pseudomonas aeruginosa. (26th August 2014) - Wagemans, Jeroen; Blasdel, Bob G.; Van den Bossche, An; Uytterhoeven, Birgit; De Smet, Jeroen; Paeshuyse, Jan; Cenens, William; Aertsen, Abram; Uetz, Peter; Delattre, Anne‐Sophie; Ceyssens, Pieter‐Jan; Lavigne, Rob
Summary Immediately after infection, virulent bacteriophages hijack the molecular machinery of their bacterial host to create an optimal climate for phage propagation. For the vast majority of known phages, it is completely unknown which bacterial functions are inhibited or coopted. Early expressed phage genome regions are rarely identified, and often filled with small genes with no homology in databases (so‐called ORFans). In this work, we first analysed the temporal transcription pattern of the N4‐like Pseudomonas‐infecting phages and selected 26 unknown, early phage ORFans. By expressing their encoded proteins individually in the host bacterium Pseudomonas aeruginosa, we identified and further characterized six antibacterial early phage proteins using time‐lapse microscopy, radioactive labelling and pull‐down experiments. Yeast two‐hybrid analysis gaveclues to their possible role in phage infection. Specifically, we show that the inhibitory proteins may interact with transcriptional regulator PA0120, the replicative DNA helicase DnaB, the riboflavin metabolism key enzyme RibB, the ATPase PA0657and the spermidine acetyltransferase PA4114. The dependency of phage infection on spermidine was shown in a final experiment. In the future, knowledge of how phages shut down their hosts as well ass novel phage–host interaction partners could be very valuable in the identification of novel antibacterial targets.